Implementasi Teori Belajar Bermakna David Ausubel Dalam Pembelajaran Pendidikan Agama Islam - Dadan Nugraha; Firgina Amelia Nur Husni (Bildung: Jurnal Ilmu Pendidikan, 2025)
This study aims to determine the process of implementing David Ausubel's learning theory in Islamic Religious Education learning at the Samin School of the Odesa Foundation in Cikadut Village, Cimenyan District, Bandung Regency. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through observation, interviews, and documentation. In implementing David Ausubel's meaningful learning theory in Islamic religious education learning, especially in ethics and moral education, two stages are used, namely the first, the planning stage. The results of the study show that the planning process begins with knowing the background knowledge of students where it is seen that the low understanding of ethics and manners is shown through the attitudes of students so that it is necessary to instill these Islamic values. The stage or process of implementing Islamic religious education learning is carried out through audio-visual, this is because students are so enthusiastic to participate in the teaching and learning process, so they can easily understand the teaching material after repeating the material using the question and answer method.